High-strength, high-conductivity and heat-resistant aluminum-based composite material and preparation method thereof

Through the composite sintering of the aluminum alloy matrix with the conductive fiber membrane, and elements such as Zr, Hf and B are added, combined with centrifugal atomization method and electrospinning method, the shortcomings of existing aluminum materials in terms of high conductivity, heat resistance, corrosion resistance and mechanical properties are solved, and a high-strength, high-conductive, heat-resistant aluminum-based composite material is realized.

CN119876793APending Publication Date: 2025-04-25SHANDONG INNOVATION PRECISION TECH CO LTD
View PDF 0 Cites 3 Cited by

Patent Information

Application Number
CN202410823567.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-06-25
Publication Date
2025-04-25

AI Technical Summary

Technical Problem

Existing aluminum materials are difficult to meet the requirements of high conductivity, heat resistance, corrosion resistance and excellent mechanical properties, especially under complex use conditions.

Method used

The method of composite sintering of aluminum alloy matrix and conductive fiber membranes is adopted, and high-strength, high-conductive and heat-resistant aluminum composite materials are prepared by adding elements such as Zr, Hf and B, combined with centrifugal atomization method and electrospinning method.

Benefits of technology

The high conductivity, heat resistance and comprehensive mechanical properties of the material are improved, and good conductivity and mechanical properties can be maintained at high temperatures.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004909793680000131
    Figure BDA0004909793680000131
Patent Text Reader

Abstract

The invention discloses a high-strength, high-conductivity and heat-resistant aluminum-based composite material. The aluminum-based composite material is formed by compounding and sintering 90-95 wt% of an aluminum alloy matrix and 5-10 wt% of a conductive fiber membrane. A trace amount of Zr, Hf and B elements are added into the aluminum alloy matrix, and the effects of refining grains, purifying impurities and improving the electric conductivity, heat resistance and comprehensive mechanical performance of the alloy matrix can be achieved. The conductive fiber membrane is a polyaniline / polyacrylonitrile composite conductive fiber membrane doped with nano-copper particles and cerium oxide particles, and polyaniline and polyacrylonitrile blended spinning can improve the strength and stability of the fiber membrane. And the conductivity of the fiber membrane and the bonding strength of the fiber membrane and an aluminum alloy matrix can be further improved through doping of the nano-copper particles and the cerium oxide particles. The aluminum-based composite material disclosed by the invention has good electrical conductivity and heat resistance and excellent comprehensive mechanical properties.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of alloys, and in particular to a high-strength, high-conductivity, and heat-resistant aluminum-based composite material. Background Art

[0002] Aluminum is the most abundant metal element in the earth's crust, so aluminum material has low cost, low density, good electrical and thermal conductivity and formability, etc. It is currently widely used in power cables, gradually replacing copper with aluminum. With the increase in electricity demand and changes in the service environment, the performance requirements for aluminum materials are gradually increasing. As a conductive material, it is not only required to have high conductivity, but also good heat and corrosion resistance, as well as excellent mechanical properties, which is of great significance to energy conservation and environmental protection, as well as improving the efficiency of power transportation. With the development of science and technology and economy, the functions of products are increasing, the conditions of use are becoming more complex, and the requirements for material performance are becoming higher and higher. Traditional aluminum alloy materials are difficult to meet the performance requirements of products, so composite materials based on aluminum and aluminum alloys have attracted widespread attention. Aluminum-based composite materials can not only retain the characteristics of aluminum alloys with a wide range of applications and good processing and forming performance, but also can obtain good physical, chemical and mechanical properties by adding reinforcement phases of different properties and forms, thereby expanding the application range of aluminum materials and obtaining good economic and social benefits. Summary of the invention

[0003] Technical problem to be solved: The technical problem to be solved by the present invention is to provide a high-strength, high-conductivity and heat-resistant aluminum-based composite material.

[0004] Technical solution: A high-strength, high-conductivity and heat-resistant aluminum-based composite material, composed of an aluminum alloy matrix and a conductive fiber membrane, including 90-95wt% of aluminum alloy and 5-10wt% of conductive fiber membrane. Preferably, the preparation method of the aluminum-based composite material is a plasma spark sintering method, comprising the following steps: S1. Mixing: aluminum alloy particles and conductive fiber membranes are configured in proportion, placed in a ball mill, filled with argon and sealed, and mixed by low-speed ball milling to obtain a uniformly mixed powder; S2. Pre-pressing, placing the uniformly mixed powder into a mold, applying pre-pressure to compact the powder to obtain a pre-pressed green body; S3. Sintering: placing the green body into a plasma discharge sintering furnace, pressurizing and evacuating the furnace, performing discharge sintering and keeping warm, and taking it out after the furnace cools to room temperature to obtain a high-strength, high-conductivity, and heat-resistant aluminum-based composite material. Preferably, the aluminum alloy particles in step S1 have a particle size range of 20 to 40 μm, and the conductive fiber membrane is in the shape of a disc with a diameter of 3 to 7 mm and a thickness of 10 to 20 μm. Preferably, the sintering temperature in step S3 is 550-600° C., the pressure during the sintering process is 40-50 MPa, and the holding time is 10-20 min. Preferably, the composition of the aluminum alloy matrix consists of the following weight ratios: Mg: 0.6~1.0wt%, Cu: 0.7~1.1wt%, Fe: ≤0.1wt%, Zr: 0.08~0.18wt%, Hf: 0.05~0.1wt%, B: 0.02~0.04wt%, and the balance is Al. Preferably, the aluminum alloy powder is prepared by centrifugal atomization, comprising the following steps: S11. Ingredients: calculate and weigh the required mass of each raw material according to the percentage to obtain the configured raw materials; S12. Melting, placing the configured raw materials into a smelting furnace, vacuuming and heating to a molten state, and introducing the alloy melt into an atomizer through a heating and insulation delivery pipe; S13. Centrifugal atomization, filling with nitrogen as a protective gas, sending the alloy melt to the high-speed rotating atomization disk, forming spherical powder under the action of centrifugation, collecting and sieving to obtain aluminum alloy powder. Preferably, the conductive fiber membrane is a polyaniline / polyacrylonitrile composite conductive fiber membrane doped with nano copper particles and cerium oxide particles. Preferably, the conductive fiber membrane is prepared by an electrospinning method, comprising the following steps: S21. Preparation of spinning solution: polyaniline powder, copper nitrate crystals and cerium oxide particles are dissolved in dimethylacetamide solution and ultrasonically dispersed, polyacrylonitrile is added and stirred until completely dissolved to obtain a polyaniline / polyacrylonitrile spinning solution containing copper nitrate crystals and cerium oxide particles; S22. electrospinning, pouring the spinning solution into a syringe, adjusting the process parameters for spinning, and obtaining a polyaniline / polyacrylonitrile composite conductive fiber membrane doped with copper nitrate and cerium oxide; S23. Reduction, placing the fiber membrane loaded with cerium oxide and copper nitrate into a hydrazine hydrate solution for immersion reduction, and after the reaction is completed, washing, ultrasonic treatment and drying are performed to obtain a polyaniline / polyacrylonitrile composite conductive fiber membrane doped with nano-copper particles and cerium oxide particles. Preferably, in step S21, the mass ratio of polyaniline to polyacrylonitrile is 1:4-10, and in step S23, the mass fractions of nano copper particles and cerium oxide particles are 0.8-1.5wt% and 0.3-0.5wt% respectively. Preferably, in step S22, the spinning voltage is 12-15 kV, the spinning solution flow rate is 0.8-1.2 mL / h, the receiving distance is 18-22 cm, and the receiver rotation speed is 120-180 r / min. Beneficial effects: Compared with the prior art, the present invention has the following characteristics: The aluminum-based composite material of the present invention is formed by composite sintering of an aluminum alloy matrix and a conductive fiber membrane, and has good electrical conductivity, heat resistance and excellent comprehensive mechanical properties. Adding trace amounts of Zr and Hf elements to the aluminum alloy matrix can play a role in refining the grains, and also precipitate fine and dispersed Al3Zr phase and Al3Hf phase, which can hinder dislocation movement and prevent grain coarsening caused by alloy recrystallization at high temperature. It is the main strengthening method for high-temperature resistant conductive aluminum alloys, and can also improve the oxidation resistance, corrosion resistance and mechanical properties of aluminum alloys. The B element can react with the impurity elements in the aluminum alloy matrix to generate borides, so that the impurities are converted from the solid solution state to the precipitation state, purify the alloy matrix, reduce the lattice distortion of the alloy caused by the solid solution of impurities, eliminate its adverse effect on conductivity, and can also generate Al-B intermediate alloys, which play a role in refining the alloy grains. In addition, the aluminum alloy particles are prepared by centrifugal atomization, and the metal melt is dispersed into small droplets by centrifugal force, and then solidified into alloy particles. Due to the fast solidification speed, the generated grain size is small and the impurities are few, and the alloy performance can be significantly improved. In addition, the alloy particles prepared by the centrifugal atomization method have a high powder yield and good sphericity, which is conducive to the subsequent sintering process. The conductive fiber membrane is prepared by electrospinning, and polyaniline and polyacrylonitrile are mixed and co-spun to prepare a flexible conductive fiber membrane. Single polyaniline has a high conductivity, but poor solubility and stability, and the mechanical properties of the obtained fiber are not high. Using polyacrylonitrile as the matrix polymer and co-spinning with polyaniline can improve the strength and stability of the fiber membrane while ensuring the conductivity of the fiber membrane. Adding conductive filler nano copper particles and cerium oxide particles to the blended fiber membrane can improve the conductivity of the fiber membrane and make up for the decrease in conductivity caused by co-spinning. The conductive fiber membrane has good flexibility and tensile strength. Composite with aluminum alloy matrix can improve its mechanical properties while ensuring that the conductive properties of the material do not decrease. The nano copper particles and cerium oxide particles doped in the fiber membrane can improve the bonding strength between the alloy matrix and the fiber membrane. Rare earth oxides can purify the alloy melt and improve the comprehensive performance of the composite material. Compared with the prior art, the present invention has the following advantages and positive effects: The invention is composited by an aluminum alloy matrix and a conductive fiber membrane, which ensures good conductivity of the aluminum-based composite material and is beneficial to improving the mechanical properties and heat resistance of the material. The aluminum alloy matrix of the present invention is doped with elements such as Zr, Hf, and B, which is beneficial to improving the electrical conductivity and heat resistance of the material. The alloy particles prepared by the centrifugal atomization method have good sphericity, fine grains, and excellent mechanical properties. The conductive fiber membrane of the present invention is doped with nano copper particles and cerium oxide particles, which can enhance the bonding strength between the fiber membrane and the aluminum alloy matrix while improving the conductive properties of the material. In addition, rare earth is beneficial to improving the alloy structure and improving the overall performance. DETAILED DESCRIPTION In order to further understand the present invention, preferred embodiments of the present invention are described below in conjunction with examples. Specific preferred examples are as follows: Embodiment 1: A high-strength, high-conductivity, and heat-resistant aluminum-based composite material, consisting of an aluminum alloy matrix and a conductive fiber membrane, including 90wt% of aluminum alloy and 10wt% of conductive fiber membrane; The preparation method of the aluminum-based composite material is a plasma discharge sintering method, which comprises the following steps: S1. Mixing: aluminum alloy particles and conductive fiber membranes are configured in proportion, placed in a ball mill, filled with argon and sealed, and mixed by low-speed ball milling to obtain a uniformly mixed powder; S2. Pre-pressing, placing the uniformly mixed powder into a mold, applying pre-pressure to compact the powder to obtain a pre-pressed green body; S3. Sintering, placing the green body into a plasma discharge sintering furnace, pressurizing and evacuating, discharge sintering and heat preservation, the sintering temperature is 600 ° C, the pressure during sintering is 50 MPa, the heat preservation time is 10 min, and the furnace is cooled to room temperature and then taken out to obtain a high-strength, high-conductivity and heat-resistant aluminum-based composite material; The aluminum alloy particles in step S1 have a particle size range of 20 to 40 μm, and the conductive fiber membrane is in the shape of a disc with a diameter of 5 to 7 mm and a thickness of 20 μm; The composition of the aluminum alloy matrix is ​​composed of the following weight ratios: Mg: 0.6wt%, Cu: 1.1wt%, Fe: 0.02wt%, Zr: 0.08wt%, Hf: 0.1wt%, B: 0.02wt%, the balance is Al; The preparation method of the aluminum alloy powder is a centrifugal atomization method, comprising the following steps: S11. Ingredients: calculate and weigh the required mass of each raw material according to the percentage to obtain the configured raw materials; S12. Melting, placing the configured raw materials into a smelting furnace, vacuuming and heating to a molten state, and introducing the alloy melt into an atomizer through a heating and insulation delivery pipe; S13 centrifugal atomization, nitrogen is filled as a protective gas, the alloy melt is sent to a high-speed rotating atomization disk, spherical powder is formed under the action of centrifugation, and the aluminum alloy powder is collected and sieved; The conductive fiber membrane is a polyaniline / polyacrylonitrile composite conductive fiber membrane doped with nano copper particles and cerium oxide particles; The preparation method of the conductive fiber membrane is an electrostatic spinning method, which comprises the following steps: S21. Preparation of spinning solution: dissolving polyaniline powder, copper nitrate crystals and cerium oxide particles in dimethylacetamide solution by ultrasonic dispersion, adding polyacrylonitrile and stirring until completely dissolved, the mass ratio of polyaniline to polyacrylonitrile being 1:4, and obtaining a polyaniline / polyacrylonitrile spinning solution containing copper nitrate crystals and cerium oxide particles; S22. Electrospinning, pouring the spinning solution into a syringe for spinning, the spinning voltage is 12 kV, the spinning solution flow rate is 0.8 mL / h, the receiving distance is 18 cm, the receiver speed is 120 r / min, and a polyaniline / polyacrylonitrile composite conductive fiber membrane doped with copper nitrate and cerium oxide is obtained; S23. Reduction: The fiber membrane loaded with cerium oxide and copper nitrate is immersed in a hydrazine hydrate solution for reduction. After the reaction is completed, it is cleaned, ultrasonically treated and then dried to obtain a polyaniline / polyacrylonitrile composite conductive fiber membrane doped with nano-copper particles and cerium oxide particles. The mass fractions of the nano-copper particles and the cerium oxide particles are 1.5wt% and 0.3wt%, respectively. Embodiment 2: A high-strength, high-conductivity, heat-resistant aluminum-based composite material, consisting of an aluminum alloy matrix and a conductive fiber membrane, including 95wt% of aluminum alloy and 5wt% of conductive fiber membrane; The preparation method of the aluminum-based composite material is a plasma discharge sintering method, which comprises the following steps: S1. Mixing: aluminum alloy particles and conductive fiber membranes are configured in proportion, placed in a ball mill, filled with argon and sealed, and mixed by low-speed ball milling to obtain a uniformly mixed powder; S2. Pre-pressing, placing the uniformly mixed powder into a mold, applying pre-pressure to compact the powder to obtain a pre-pressed green body; S3. Sintering, placing the green body into a plasma discharge sintering furnace, pressurizing and evacuating, discharge sintering and heat preservation, the sintering temperature is 550 ° C, the pressure during sintering is 50 MPa, the heat preservation time is 20 min, and the furnace is cooled to room temperature and then taken out to obtain a high-strength, high-conductivity and heat-resistant aluminum-based composite material; The aluminum alloy particles in step S1 have a particle size range of 20 to 40 μm, and the conductive fiber membrane is in the shape of a disc with a diameter of 3 to 5 mm and a thickness of 10 μm; The composition of the aluminum alloy matrix is ​​composed of the following weight ratios: Mg: 1.0wt%, Cu: 0.7wt%, Fe: 0.1wt%, Zr: 0.18wt%, Hf: 0.05wt%, B: 0.04wt%, the balance is Al; The preparation method of the aluminum alloy powder is a centrifugal atomization method, comprising the following steps: S11. Ingredients: calculate and weigh the required mass of each raw material according to the percentage to obtain the configured raw materials; S12. Melting, placing the configured raw materials into a smelting furnace, vacuuming and heating to a molten state, and introducing the alloy melt into an atomizer through a heating and insulation delivery pipe; S13 centrifugal atomization, nitrogen is filled as a protective gas, the alloy melt is sent to a high-speed rotating atomization disk, spherical powder is formed under the action of centrifugation, and the aluminum alloy powder is collected and sieved; The conductive fiber membrane is a polyaniline / polyacrylonitrile composite conductive fiber membrane doped with nano copper particles and cerium oxide particles; The preparation method of the conductive fiber membrane is an electrostatic spinning method, which comprises the following steps: S21. Preparation of spinning solution: dissolving polyaniline powder, copper nitrate crystals and cerium oxide particles in dimethylacetamide solution by ultrasonic dispersion, adding polyacrylonitrile and stirring until completely dissolved, the mass ratio of polyaniline to polyacrylonitrile being 1:10, and obtaining a polyaniline / polyacrylonitrile spinning solution containing copper nitrate crystals and cerium oxide particles; S22. Electrospinning, pouring the spinning solution into a syringe for spinning, the spinning voltage is 15 kV, the spinning solution flow rate is 1.2 mL / h, the receiving distance is 22 cm, the receiver speed is 180 r / min, and a polyaniline / polyacrylonitrile composite conductive fiber membrane doped with copper nitrate and cerium oxide is obtained; S23. Reduction: The fiber membrane loaded with cerium oxide and copper nitrate is immersed in a hydrazine hydrate solution for reduction. After the reaction is completed, it is cleaned, ultrasonically treated and then dried to obtain a polyaniline / polyacrylonitrile composite conductive fiber membrane doped with nano-copper particles and cerium oxide particles. The mass fractions of the nano-copper particles and the cerium oxide particles are 0.8wt% and 0.5wt%, respectively. Embodiment 3: A high-strength, high-conductivity, heat-resistant aluminum-based composite material, consisting of an aluminum alloy matrix and a conductive fiber membrane, including 92wt% of aluminum alloy and 8wt% of conductive fiber membrane; The preparation method of the aluminum-based composite material is a plasma discharge sintering method, which comprises the following steps: S1. Mixing: aluminum alloy particles and conductive fiber membranes are configured in proportion, placed in a ball mill, filled with argon and sealed, and mixed by low-speed ball milling to obtain a uniformly mixed powder; S2. Pre-pressing, placing the uniformly mixed powder into a mold, applying pre-pressure to compact the powder to obtain a pre-pressed green body; S3. Sintering, placing the green body into a plasma discharge sintering furnace, pressurizing and evacuating, discharge sintering and heat preservation, the sintering temperature is 580 ° C, the pressure during sintering is 42 MPa, the heat preservation time is 17 min, and the furnace is cooled to room temperature and then taken out to obtain a high-strength, high-conductivity and heat-resistant aluminum-based composite material; The aluminum alloy particles in step S1 have a particle size range of 20 to 40 μm, and the conductive fiber membrane is in the shape of a disc with a diameter of 4 to 6 mm and a thickness of 15 μm; The composition of the aluminum alloy matrix is ​​composed of the following weight ratios: Mg: 0.9wt%, Cu: 0.8wt%, Fe: 0.07wt%, Zr: 0.14wt%, Hf: 0.06wt%, B: 0.03wt%, the balance is Al; The preparation method of the aluminum alloy powder is a centrifugal atomization method, comprising the following steps: S11. Ingredients: calculate and weigh the required mass of each raw material according to the percentage to obtain the configured raw materials; S12. Melting, placing the configured raw materials into a smelting furnace, vacuuming and heating to a molten state, and introducing the alloy melt into an atomizer through a heating and insulation delivery pipe; S13 centrifugal atomization, nitrogen is filled as a protective gas, the alloy melt is sent to a high-speed rotating atomization disk, spherical powder is formed under the action of centrifugation, and the aluminum alloy powder is collected and sieved; The conductive fiber membrane is a polyaniline / polyacrylonitrile composite conductive fiber membrane doped with nano copper particles and cerium oxide particles; The preparation method of the conductive fiber membrane is an electrostatic spinning method, which comprises the following steps: S21. Preparation of spinning solution: dissolving polyaniline powder, copper nitrate crystals and cerium oxide particles in dimethylacetamide solution by ultrasonic dispersion, adding polyacrylonitrile and stirring until completely dissolved, the mass ratio of polyaniline to polyacrylonitrile being 1:8, and obtaining a polyaniline / polyacrylonitrile spinning solution containing copper nitrate crystals and cerium oxide particles; S22. Electrospinning, pouring the spinning solution into a syringe for spinning, the spinning voltage is 14 kV, the spinning solution flow rate is 1.0 mL / h, the receiving distance is 21 cm, the receiver speed is 140 r / min, and a polyaniline / polyacrylonitrile composite conductive fiber membrane doped with copper nitrate and cerium oxide is obtained; S23. Reduction: The fiber membrane loaded with cerium oxide and copper nitrate is immersed in a hydrazine hydrate solution for reduction. After the reaction is completed, it is cleaned, ultrasonically treated and then dried to obtain a polyaniline / polyacrylonitrile composite conductive fiber membrane doped with nano-copper particles and cerium oxide particles. The mass fractions of the nano-copper particles and the cerium oxide particles are 1.1wt% and 0.45wt%, respectively. Embodiment 4: A high-strength, high-conductivity, heat-resistant aluminum-based composite material, consisting of an aluminum alloy matrix and a conductive fiber membrane, including 94wt% of aluminum alloy and 6wt% of conductive fiber membrane; The preparation method of the aluminum-based composite material is a plasma discharge sintering method, which comprises the following steps: S1. Mixing: aluminum alloy particles and conductive fiber membranes are configured in proportion, placed in a ball mill, filled with argon and sealed, and mixed by low-speed ball milling to obtain a uniformly mixed powder; S2. Pre-pressing, placing the uniformly mixed powder into a mold, applying pre-pressure to compact the powder to obtain a pre-pressed green body; S3. Sintering, placing the green body into a plasma discharge sintering furnace, pressurizing and evacuating, discharge sintering and heat preservation, the sintering temperature is 560 ° C, the pressure during sintering is 45 MPa, the heat preservation time is 13 min, and the furnace is cooled to room temperature and then taken out to obtain a high-strength, high-conductivity and heat-resistant aluminum-based composite material; The aluminum alloy particles in step S1 have a particle size range of 20 to 40 μm, and the conductive fiber membrane is in the shape of a disc with a diameter of 3 to 5 mm and a thickness of 18 μm; The composition of the aluminum alloy matrix is ​​composed of the following weight ratios: Mg: 0.7wt%, Cu: 1.0wt%, Fe: 0.05wt%, Zr: 0.11wt%, Hf: 0.07wt%, B: 0.02wt%, the balance is Al; The preparation method of the aluminum alloy powder is a centrifugal atomization method, comprising the following steps: S11. Ingredients: calculate and weigh the required mass of each raw material according to the percentage to obtain the configured raw materials; S12. Melting, placing the configured raw materials into a smelting furnace, vacuuming and heating to a molten state, and introducing the alloy melt into an atomizer through a heating and insulation delivery pipe; S13 centrifugal atomization, nitrogen is filled as a protective gas, the alloy melt is sent to a high-speed rotating atomization disk, spherical powder is formed under the action of centrifugation, and the aluminum alloy powder is collected and sieved; The conductive fiber membrane is a polyaniline / polyacrylonitrile composite conductive fiber membrane doped with nano copper particles and cerium oxide particles; The preparation method of the conductive fiber membrane is an electrostatic spinning method, which comprises the following steps: S21. Preparation of spinning solution: dissolving polyaniline powder, copper nitrate crystals and cerium oxide particles in dimethylacetamide solution by ultrasonic dispersion, adding polyacrylonitrile and stirring until completely dissolved, the mass ratio of polyaniline to polyacrylonitrile being 1:6, and obtaining a polyaniline / polyacrylonitrile spinning solution containing copper nitrate crystals and cerium oxide particles; S22. Electrospinning, pouring the spinning solution into a syringe for spinning, the spinning voltage is 13 kV, the spinning solution flow rate is 1.1 mL / h, the receiving distance is 19 cm, the receiver speed is 160 r / min, and a polyaniline / polyacrylonitrile composite conductive fiber membrane doped with copper nitrate and cerium oxide is obtained; S23. Reduction: The fiber membrane loaded with cerium oxide and copper nitrate is immersed in a hydrazine hydrate solution for reduction. After the reaction is completed, it is cleaned, ultrasonically treated and then dried to obtain a polyaniline / polyacrylonitrile composite conductive fiber membrane doped with nano-copper particles and cerium oxide particles. The mass fractions of the nano-copper particles and the cerium oxide particles are 1.3wt% and 0.35wt%, respectively. Embodiment 5: A high-strength, high-conductivity, heat-resistant aluminum-based composite material, consisting of an aluminum alloy matrix and a conductive fiber membrane, including 93wt% of aluminum alloy and 7wt% of conductive fiber membrane; The preparation method of the aluminum-based composite material is a plasma discharge sintering method, which comprises the following steps: S1. Mixing: aluminum alloy particles and conductive fiber membranes are configured in proportion, placed in a ball mill, filled with argon and sealed, and mixed by low-speed ball milling to obtain a uniformly mixed powder; S2. Pre-pressing, placing the uniformly mixed powder into a mold, applying pre-pressure to compact the powder to obtain a pre-pressed green body; S3. Sintering, placing the green body into a plasma discharge sintering furnace, pressurizing and evacuating, discharge sintering and heat preservation, the sintering temperature is 570 ° C, the pressure during sintering is 48 MPa, the heat preservation time is 15 min, and the furnace is cooled to room temperature and then taken out to obtain a high-strength, high-conductivity and heat-resistant aluminum-based composite material; The aluminum alloy particles in step S1 have a particle size range of 20 to 40 μm, and the conductive fiber membrane is in the shape of a disc with a diameter of 5 to 7 mm and a thickness of 12 μm; The composition of the aluminum alloy matrix is ​​composed of the following weight ratios: Mg: 0.8wt%, Cu: 0.9wt%, Fe: 0.03wt%, Zr: 0.16wt%, Hf: 0.09wt%, B: 0.02wt%, the balance is Al; The preparation method of the aluminum alloy powder is a centrifugal atomization method, comprising the following steps: S11. Ingredients: calculate and weigh the required mass of each raw material according to the percentage to obtain the configured raw materials; S12. Melting, placing the configured raw materials into a smelting furnace, vacuuming and heating to a molten state, and introducing the alloy melt into an atomizer through a heating and insulation delivery pipe; S13 centrifugal atomization, nitrogen is filled as a protective gas, the alloy melt is sent to a high-speed rotating atomization disk, spherical powder is formed under the action of centrifugation, and the aluminum alloy powder is collected and sieved; The conductive fiber membrane is a polyaniline / polyacrylonitrile composite conductive fiber membrane doped with nano copper particles and cerium oxide particles; The preparation method of the conductive fiber membrane is an electrostatic spinning method, which comprises the following steps: S21. Preparation of spinning solution: dissolving polyaniline powder, copper nitrate crystals and cerium oxide particles in dimethylacetamide solution by ultrasonic dispersion, adding polyacrylonitrile and stirring until completely dissolved, wherein the mass ratio of polyaniline to polyacrylonitrile is 1:7, and obtaining a polyaniline / polyacrylonitrile spinning solution containing copper nitrate crystals and cerium oxide particles; S22. Electrospinning, pouring the spinning solution into a syringe for spinning, the spinning voltage is 15 kV, the spinning solution flow rate is 0.9 mL / h, the receiving distance is 20 cm, the receiver speed is 150 r / min, and a polyaniline / polyacrylonitrile composite conductive fiber membrane doped with copper nitrate and cerium oxide is obtained; S23. Reduction: The fiber membrane loaded with cerium oxide and copper nitrate is immersed in a hydrazine hydrate solution for reduction. After the reaction is completed, it is cleaned, ultrasonically treated and then dried to obtain a polyaniline / polyacrylonitrile composite conductive fiber membrane doped with nano-copper particles and cerium oxide particles. The mass fractions of the nano-copper particles and the cerium oxide particles are 0.9wt% and 0.4wt%, respectively. Comparative Example 1: An aluminum-based composite material, consisting of an aluminum alloy matrix and a conductive fiber membrane, including 91wt% of aluminum alloy and 9wt% of conductive fiber membrane; The preparation method of the aluminum-based composite material is a plasma discharge sintering method, which comprises the following steps: S1. Mixing: aluminum alloy particles and conductive fiber membranes are configured in proportion, placed in a ball mill, filled with argon and sealed, and mixed by low-speed ball milling to obtain a uniformly mixed powder; S2. Pre-pressing, placing the uniformly mixed powder into a mold, applying pre-pressure to compact the powder to obtain a pre-pressed green body; S3. Sintering, placing the green body into a plasma discharge sintering furnace, pressurizing and evacuating, discharge sintering and heat preservation, the sintering temperature is 590 ° C, the pressure during the sintering process is 47 MPa, the heat preservation time is 12 min, and the furnace is cooled to room temperature and then taken out to obtain a high-strength, high-conductivity and heat-resistant aluminum-based composite material; The aluminum alloy particles in step S1 have a particle size range of 20 to 40 μm, and the conductive fiber membrane is in the shape of a disc with a diameter of 4 to 6 mm and a thickness of 16 μm; The composition of the aluminum alloy matrix is ​​composed of the following weight ratios: Mg: 0.6wt%, Cu: 1.1wt%, Fe: 0.08wt%, the balance is Al; The preparation method of the aluminum alloy powder is a centrifugal atomization method, comprising the following steps: S11. Ingredients: calculate and weigh the required mass of each raw material according to the percentage to obtain the configured raw materials; S12. Melting, placing the configured raw materials into a smelting furnace, vacuuming and heating to a molten state, and introducing the alloy melt into an atomizer through a heating and insulation delivery pipe; S13 centrifugal atomization, nitrogen is filled as a protective gas, the alloy melt is sent to a high-speed rotating atomization disk, spherical powder is formed under the action of centrifugation, and the aluminum alloy powder is collected and sieved; The conductive fiber membrane is a polyaniline / polyacrylonitrile composite conductive fiber membrane doped with nano copper particles and cerium oxide particles; The preparation method of the conductive fiber membrane is an electrostatic spinning method, which comprises the following steps: S21. Preparation of spinning solution: dissolving polyaniline powder, copper nitrate crystals and cerium oxide particles in dimethylacetamide solution by ultrasonic dispersion, adding polyacrylonitrile and stirring until completely dissolved, the mass ratio of polyaniline to polyacrylonitrile being 1:5, and obtaining a polyaniline / polyacrylonitrile spinning solution containing copper nitrate crystals and cerium oxide particles; S22. Electrospinning, pouring the spinning solution into a syringe for spinning, the spinning voltage is 12 kV, the spinning solution flow rate is 1.0 mL / h, the receiving distance is 19 cm, the receiver speed is 130 r / min, and a polyaniline / polyacrylonitrile composite conductive fiber membrane doped with copper nitrate and cerium oxide is obtained; S23. Reduction: The fiber membrane loaded with cerium oxide and copper nitrate is immersed in a hydrazine hydrate solution for reduction. After the reaction is completed, it is cleaned, ultrasonically treated and then dried to obtain a polyaniline / polyacrylonitrile composite conductive fiber membrane doped with nano-copper particles and cerium oxide particles. The mass fractions of the nano-copper particles and the cerium oxide particles are 0.9wt% and 0.45wt%, respectively. Comparative Example 2: An aluminum-based composite material, consisting of an aluminum alloy matrix and a conductive fiber membrane, including 85wt% of aluminum alloy and 15wt% of conductive fiber membrane; The preparation method of the aluminum-based composite material is a plasma discharge sintering method, which comprises the following steps: S1. Mixing: aluminum alloy particles and conductive fiber membranes are configured in proportion, placed in a ball mill, filled with argon and sealed, and mixed by low-speed ball milling to obtain a uniformly mixed powder; S2. Pre-pressing, placing the uniformly mixed powder into a mold, applying pre-pressure to compact the powder to obtain a pre-pressed green body; S3. Sintering, placing the green body into a plasma discharge sintering furnace, pressurizing and evacuating, discharge sintering and heat preservation, the sintering temperature is 600 ° C, the pressure during sintering is 49 MPa, the heat preservation time is 14 min, and the furnace is cooled to room temperature and then taken out to obtain a high-strength, high-conductivity and heat-resistant aluminum-based composite material; The aluminum alloy particles in step S1 have a particle size range of 20 to 40 μm, and the conductive fiber membrane is in the shape of a disc with a diameter of 5 to 7 mm and a thickness of 25 μm; The composition of the aluminum alloy matrix is ​​composed of the following weight ratios: Mg: 0.8wt%, Cu: 1.0wt%, Fe: 0.04wt%, Zr: 0.13wt%, Hf: 0.08wt%, B: 0.03wt%, the balance is Al; The preparation method of the aluminum alloy powder is a centrifugal atomization method, comprising the following steps: S11. Ingredients: calculate and weigh the required mass of each raw material according to the percentage to obtain the configured raw materials; S12. Melting, placing the configured raw materials into a smelting furnace, vacuuming and heating to a molten state, and introducing the alloy melt into an atomizer through a heating and insulation delivery pipe; S13 centrifugal atomization, nitrogen is filled as a protective gas, the alloy melt is sent to a high-speed rotating atomization disk, spherical powder is formed under the action of centrifugation, and the aluminum alloy powder is collected and sieved; The conductive fiber membrane is a polyaniline / polyacrylonitrile composite conductive fiber membrane doped with nano copper particles and cerium oxide particles; The preparation method of the conductive fiber membrane is an electrostatic spinning method, which comprises the following steps: S21. Preparation of spinning solution: dissolving polyaniline powder, copper nitrate crystals and cerium oxide particles in dimethylacetamide solution by ultrasonic dispersion, adding polyacrylonitrile and stirring until completely dissolved, wherein the mass ratio of polyaniline to polyacrylonitrile is 1:7, and obtaining a polyaniline / polyacrylonitrile spinning solution containing copper nitrate crystals and cerium oxide particles; S22. Electrospinning, pouring the spinning solution into a syringe for spinning, the spinning voltage is 15 kV, the spinning solution flow rate is 0.8 mL / h, the receiving distance is 20 cm, the receiver speed is 140 r / min, and a polyaniline / polyacrylonitrile composite conductive fiber membrane doped with copper nitrate and cerium oxide is obtained; S23. Reduction: The fiber membrane loaded with cerium oxide and copper nitrate is immersed in a hydrazine hydrate solution for reduction. After the reaction is completed, it is cleaned, ultrasonically treated and then dried to obtain a polyaniline / polyacrylonitrile composite conductive fiber membrane doped with nano-copper particles and cerium oxide particles. The mass fractions of the nano-copper particles and the cerium oxide particles are 1.0wt% and 0.4wt%, respectively. Comparative Example 3: An aluminum-based composite material, consisting of an aluminum alloy matrix and a conductive fiber membrane, including 95wt% of aluminum alloy and 5wt% of conductive fiber membrane; The preparation method of the aluminum-based composite material is a plasma discharge sintering method, which comprises the following steps: S1. Mixing: aluminum alloy particles and conductive fiber membranes are configured in proportion, placed in a ball mill, filled with argon and sealed, and mixed by low-speed ball milling to obtain a uniformly mixed powder; S2. Pre-pressing, placing the uniformly mixed powder into a mold, applying pre-pressure to compact the powder to obtain a pre-pressed green body; S3. Sintering, placing the green body into a plasma discharge sintering furnace, pressurizing and evacuating, discharge sintering and heat preservation, the sintering temperature is 560 ° C, the pressure during the sintering process is 40 MPa, the heat preservation time is 19 min, and the furnace is cooled to room temperature and then taken out to obtain a high-strength, high-conductivity and heat-resistant aluminum-based composite material; The aluminum alloy particles in step S1 have a particle size range of 40 to 45 μm, and the conductive fiber membrane is in the shape of a disc with a diameter of 3 to 5 mm and a thickness of 11 μm; The composition of the aluminum alloy matrix is ​​composed of the following weight ratios: Mg: 0.9wt%, Cu: 0.9wt%, Fe: 0.06wt%, Zr: 0.1wt%, Hf: 0.06wt%, B: 0.02wt%, the balance is Al; The preparation method of the aluminum alloy powder is a centrifugal atomization method, comprising the following steps: S11. Ingredients: calculate and weigh the required mass of each raw material according to the percentage to obtain the configured raw materials; S12. Melting, placing the configured raw materials into a smelting furnace, vacuuming and heating to a molten state, and introducing the alloy melt into an atomizer through a heating and insulation delivery pipe; S13 centrifugal atomization, nitrogen is filled as a protective gas, the alloy melt is sent to a high-speed rotating atomization disk, spherical powder is formed under the action of centrifugation, and the aluminum alloy powder is collected and sieved; The conductive fiber membrane is a polyaniline / polyacrylonitrile composite conductive fiber membrane doped with nano copper particles and cerium oxide particles; The preparation method of the conductive fiber membrane is an electrostatic spinning method, which comprises the following steps: S21. Preparation of spinning solution: dissolving polyaniline powder, copper nitrate crystals and cerium oxide particles in dimethylacetamide solution by ultrasonic dispersion, adding polyacrylonitrile and stirring until completely dissolved, wherein the mass ratio of polyaniline to polyacrylonitrile is 1:9, and obtaining a polyaniline / polyacrylonitrile spinning solution containing copper nitrate crystals and cerium oxide particles; S22. Electrospinning, pouring the spinning solution into a syringe for spinning, the spinning voltage is 14 kV, the spinning solution flow rate is 1.2 mL / h, the receiving distance is 22 cm, the receiver speed is 170 r / min, and a polyaniline / polyacrylonitrile composite conductive fiber membrane doped with copper nitrate and cerium oxide is obtained; S23. Reduction: The fiber membrane loaded with cerium oxide and copper nitrate is immersed in a hydrazine hydrate solution for reduction. After the reaction is completed, it is cleaned, ultrasonically treated and then dried to obtain a polyaniline / polyacrylonitrile composite conductive fiber membrane doped with nano-copper particles and cerium oxide particles. The mass fractions of the nano-copper particles and the cerium oxide particles are 0.14wt% and 0.3wt%, respectively. Comparative Example 4: An aluminum-based composite material, consisting of an aluminum alloy matrix and a conductive fiber membrane, including 90wt% of aluminum alloy and 10wt% of the conductive fiber membrane; The preparation method of the aluminum-based composite material is a plasma discharge sintering method, which comprises the following steps: S1. Mixing: aluminum alloy particles and conductive fiber membranes are configured in proportion, placed in a ball mill, filled with argon and sealed, and mixed by low-speed ball milling to obtain a uniformly mixed powder; S2. Pre-pressing, placing the uniformly mixed powder into a mold, applying pre-pressure to compact the powder to obtain a pre-pressed green body; S3. Sintering, placing the green body into a plasma discharge sintering furnace, pressurizing and evacuating, discharge sintering and heat preservation, the sintering temperature is 580 ° C, the pressure during sintering is 43 MPa, the heat preservation time is 11 min, and the furnace is cooled to room temperature and then taken out to obtain a high-strength, high-conductivity and heat-resistant aluminum-based composite material; The aluminum alloy particles in step S1 have a particle size range of 20 to 40 μm, and the conductive fiber membrane is in the shape of a disc with a diameter of 4 to 6 mm and a thickness of 18 μm; The composition of the aluminum alloy matrix is ​​composed of the following weight ratios: Mg: 0.7wt%, Cu: 1.1wt%, Fe: 0.1wt%, Zr: 0.09wt%, Hf: 0.09wt%, B: 0.03wt%, the balance is Al; The preparation method of the aluminum alloy powder is a centrifugal atomization method, comprising the following steps: S11. Ingredients: calculate and weigh the required mass of each raw material according to the percentage to obtain the configured raw materials; S12. Melting, placing the configured raw materials into a smelting furnace, vacuuming and heating to a molten state, and introducing the alloy melt into an atomizer through a heating and insulation delivery pipe; S13 centrifugal atomization, nitrogen is filled as a protective gas, the alloy melt is sent to a high-speed rotating atomization disk, spherical powder is formed under the action of centrifugation, and the aluminum alloy powder is collected and sieved; The conductive fiber membrane is a polyaniline / polyacrylonitrile composite conductive fiber membrane; The preparation method of the conductive fiber membrane is an electrostatic spinning method, which comprises the following steps: S21. Preparation of spinning solution: dissolving polyaniline powder in dimethylacetamide solution by ultrasonic dispersion, adding polyacrylonitrile and stirring until completely dissolved, the mass ratio of polyaniline to polyacrylonitrile is 1:5, and obtaining polyaniline / polyacrylonitrile spinning solution; S22. Electrospinning: pour the spinning solution into a syringe for spinning. The spinning voltage is 12 kV, the spinning solution flow rate is 1.0 mL / h, the receiving distance is 19 cm, and the receiver rotation speed is 130 r / min to obtain a polyaniline / polyacrylonitrile composite conductive fiber membrane. The tensile strength and conductivity of each embodiment and comparative example were tested by a universal testing machine and an eddy current conductivity meter, respectively. After being kept at 250°C for 1 hour, the samples were cooled to room temperature for tensile testing, and compared with the tensile strength before heat treatment. The strength residual rate was used as an indicator of its heat resistance performance. The test results are shown in the table. In summary, compared with the comparative examples, the embodiments of the present invention have higher conductivity and higher tensile strength at room temperature and high temperature, which shows that the present invention has excellent conductivity, heat resistance and good mechanical properties, good comprehensive performance and broad application prospects.

Claims

1. A high-strength, high-conductivity, heat-resistant aluminum-based composite material, characterized by: The high-strength, high-conductivity and heat-resistant aluminum-based composite material consists of an aluminum alloy matrix and a conductive fiber membrane, including 90-95wt% of aluminum alloy and 5-10wt% of conductive fiber membrane.

2. The method for preparing the high-strength, high-conductivity, heat-resistant aluminum-based composite material according to claim 1, characterized in that: The preparation method of the aluminum-based composite material is a plasma discharge sintering method, which comprises the following steps: S1. Mixing: aluminum alloy particles and conductive fiber membranes are configured in proportion, placed in a ball mill, filled with argon and sealed, and mixed by low-speed ball milling to obtain a uniformly mixed powder; S2. Pre-pressing, placing the uniformly mixed powder into a mold, applying pre-pressure to compact the powder to obtain a pre-pressed green body; S3. Sintering: placing the green body into a plasma discharge sintering furnace, pressurizing and evacuating the furnace, performing discharge sintering and keeping warm, and taking it out after the furnace cools to room temperature to obtain a high-strength, high-conductivity, and heat-resistant aluminum-based composite material.

3. The method for preparing the high-strength, high-conductivity, heat-resistant aluminum-based composite material according to claim 2, characterized in that: The particle size of the aluminum alloy particles in step S1 is in the range of 20 to 40 μm, and the conductive fiber membrane is in the shape of a disc with a diameter of 3 to 7 mm and a thickness of 10 to 20 μm.

4. The method for preparing the high-strength, high-conductivity, heat-resistant aluminum-based composite material according to claim 2, characterized in that: The sintering temperature in step S3 is 550-600° C., the pressure during the sintering process is 40-50 MPa, and the insulation time is 10-20 min.

5. The high-strength, high-conductivity, heat-resistant aluminum-based composite material according to claim 1, characterized in that: The composition of the aluminum alloy matrix is ​​composed of the following weight ratios: Mg: 0.6~1.0wt%, Cu: 0.7~1.1wt%, Fe: ≤0.1wt%, Zr: 0.08~0.18wt%, Hf: 0.05~0.1wt%, B: 0.02~0.04wt%, and the balance is Al.

6. The high-strength, high-conductivity, heat-resistant aluminum-based composite material according to claim 1, characterized in that: The preparation method of the aluminum alloy powder is a centrifugal atomization method, comprising the following steps: S11. Ingredients: calculate and weigh the required mass of each raw material according to the percentage to obtain the configured raw materials; S12. Melting, placing the configured raw materials into a smelting furnace, vacuuming and heating to a molten state, and introducing the alloy melt into an atomizer through a heating and insulation delivery pipe; S13. Centrifugal atomization, filling with nitrogen as a protective gas, sending the alloy melt to the high-speed rotating atomization disk, forming spherical powder under the action of centrifugation, collecting and sieving to obtain aluminum alloy powder.

7. The high-strength, high-conductivity, heat-resistant aluminum-based composite material according to claim 1, characterized in that: The conductive fiber membrane is a polyaniline / polyacrylonitrile composite conductive fiber membrane doped with nano copper particles and cerium oxide particles.

8. The high-strength, high-conductivity, heat-resistant aluminum-based composite material according to claim 1, characterized in that: The preparation method of the conductive fiber membrane is an electrostatic spinning method, which comprises the following steps: S21. Preparation of spinning solution: polyaniline powder, copper nitrate crystals and cerium oxide particles are dissolved in dimethylacetamide solution and ultrasonically dispersed, polyacrylonitrile is added and stirred until completely dissolved to obtain a polyaniline / polyacrylonitrile spinning solution containing copper nitrate crystals and cerium oxide particles; S22. electrospinning, pouring the spinning solution into a syringe, adjusting the process parameters for spinning, and obtaining a polyaniline / polyacrylonitrile composite conductive fiber membrane doped with copper nitrate and cerium oxide; S23. Reduction, placing the fiber membrane loaded with cerium oxide particles and copper nitrate into a hydrazine hydrate solution for immersion reduction, and after the reaction is completed, washing, ultrasonic treatment, and then drying to obtain a polyaniline / polyacrylonitrile composite conductive fiber membrane doped with nano-copper particles and cerium oxide particles.

9. The high-strength, high-conductivity, heat-resistant aluminum-based composite material according to claim 8, characterized in that: In step S21, the mass ratio of polyaniline to polyacrylonitrile is 1:4-10, and in step S23, the mass fractions of nano copper particles and cerium oxide particles are 0.8-1.5wt% and 0.3-0.5wt% respectively.

10. The high-strength, high-conductivity, heat-resistant aluminum-based composite material according to claim 8, characterized in that: In the step S22, the spinning voltage is 12-15 kV, the spinning solution flow rate is 0.8-1.2 mL / h, the receiving distance is 18-22 cm, and the receiver rotation speed is 120-180 r / min.

Citation Information

Cited By

  • Preparation method of 6101 aluminum alloy composite plate for new energy automobile conducting bar

    CN121696247A

  • Preparation method of 6101 aluminum alloy composite plate for new energy automobile conductive bar

    CN121696247B

  • Method for preparing aluminum anode plate of aluminum-air battery by adopting continuous extrusion technology

    CN121938830A